Foliar melatonin stimulates cotton boll distribution characteristics by modifying leaf sugar metabolism and antioxidant activities during drought conditions. Issue 1 (26th August 2021) - Khattak, Wajid Ali; He, Jiaqi; Abdalmegeed, Dyaaaldin; Hu, Wei; Wang, Youhua; Zhou, Zhiguo
Abstract: Drought is a severe abiotic stress affecting the plant's antioxidant system and interrupting compatible solute translocation processes, which leads to low productivity. Melatonin acts as a common growth regulator enhancing the plants defense system and regulates sugar metabolism in challenging environments. Melatonin treatments enable plants to be tolerant to abiotic stresses via enhancing their recovery potential, but its impact using various concentrations has not yet been studied in leaf physiological aspects when applied to cotton foliage during their peak flowering and boll loading stage. The overall objective of this research was to facilitate cotton boll distribution characteristics by modifying cotton leaf sugar metabolism and antioxidant activity by applying foliar melatonin (0, 25, 50, and 100 μmol l −1 ) under drought levels with a relative soil water content of 75%, 60%, and 45% ± 5 (FC1, FC2, and FC3, respectively). Higher rates of melatonin application (100 μmol l −1 ) enhanced boll distribution characteristics and controlled the boll shedding rate during drought conditions. An increase in melatonin rates proved to be more helpful in stimulating cotton sympodial leaf physiological attributes, including leaf gas exchange parameters, sugar metabolism, proline content, and antioxidants defense system as compared with less or no melatonin application during all FC conditions and showed the most significant effect at a higher melatonin concentration (M100) at 7–21 DAF. The total proline content and antioxidant activity were enhanced in the M100 treatment during all FC levels, which caused a reduction in the total malondialdehyde (MDA) contents and hydrogen peroxide (H2 O2 ) concentrations in cotton leaves. Moreover, sugar metabolism responsible genes GhSusA and SPS2 showed an upsurge in expression levels and enhanced sucrose degradation in M100 treatments during all FC levels. Furthermore, cotton boll attributes showed also a positive relation with leaf physiological and gas exchange attributes. The results suggested that foliar melatonin application during the flowering initiation stage improved the overall performance and is helpful for cotton crops productivity against drought stress.